2020
DOI: 10.1177/0193945920973151
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Physical Activity in Middle-aged Women with Type 2 Diabetes

Abstract: Physical activity is recommended for middle-aged women with type 2 diabetes mellitus (T2D) to improve health and prevent disease complications. However, most middle-aged women with T2D have low physical activity levels and therefore are at higher risk for T2D-associated cardiovascular complications. To explore their perceptions of physical activity and strategies for increasing participation, the investigators conducted a phenomenological study with a sample of middle-aged women with T2D using voice-recorded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In other cultures walking is simply preferred by women as the exercise of choice due to feasibility, safety and avoidance of gyms and swimming pools (123). Similar preferences for walking as physical activity have been shown in middle-aged American women, mostly due to accessibility (129). Children, although sometimes a barrier to exercise, can also be inspirations for exercise.…”
Section: Solution: Social and Culturally Competent Interventionsmentioning
confidence: 90%
See 1 more Smart Citation
“…In other cultures walking is simply preferred by women as the exercise of choice due to feasibility, safety and avoidance of gyms and swimming pools (123). Similar preferences for walking as physical activity have been shown in middle-aged American women, mostly due to accessibility (129). Children, although sometimes a barrier to exercise, can also be inspirations for exercise.…”
Section: Solution: Social and Culturally Competent Interventionsmentioning
confidence: 90%
“…In women with children who have a history of gestational diabetes, and therefore a 7-fold increased risk of developing T2D, a systematic review revealed that interventions which accounted for childcare were most effective, surpassing techniques such as education and wearable fitness devices that have had success in other populations ( 32 ). Studies in socially and culturally conservative populations have found remarkable success with walking as a method of exercise for women ( 123 , 129 ). Although, as previously noted, some families in culturally conservative Qatar still require women to be accompanied when leaving the home, there has been a national cultural shift towards more independence for women.…”
Section: Social and Cultural Barriers To Exercise In T2d And Potentia...mentioning
confidence: 99%
“…[11][12][13] Insulin secretion insufficiency of elderly diabetes patients is significantly related to body composition, obesity, and lack of PA, and PA can significantly improve the above problems. [14,15] Research shows that [16,17] PA is negatively related to the risk of diabetes, but the number of research evidence about PA and the risk of diabetes is limited, and the scientific quality of each research is uneven, so it is necessary to further explore the relationship between PA and the risk of diabetes. Therefore, the purpose of this study is to explore the correlation between the risk of diabetes and PA in middle-aged and elderly people in China and to provide a new basis for the study of PA in the prevention and treatment of diabetes in middle-aged and elderly people.…”
Section: Introductionmentioning
confidence: 99%